Formaldehyde Released from Clothing Articles and Pillowcases. Issue 4 (July 2022) - Reitz, Tracey A.; Reeder, Margo; Dang, Allice; Sarmadi, Majid
Clothing and bedding that are labeled as "wrinkle-free, " "iron-free, " or "easy-care" use formaldehyde resins that can release a significant amount of formaldehyde. For patients who are allergic to formaldehyde, this can trigger allergic contact dermatitis. Unlike many other countries, formaldehyde levels in clothing are not regulated in the United States. The purpose of this study is to measure the amount of formaldehyde released from a variety of men's dress shirts, women's clothing, children's clothing, and pillowcases, before washing and after washing using a Rotawash. This study has also looked at whether the price of an item has any correlation with the amount of formaldehyde released.